The Voice / The Gaze - Žukauskaitė, Audronė (Problemos, 2001)
The article discusses one of the main problems in contemporary philosophy: the annihilation of the modem subject and the advent of the Other. This problem is discussed in psychoanalytical context using the concepts of voice and gaze as conceptual tools. Usually understood as the characteristics of the modem subject, gaze and voice become the instrument of the Other’s will. The experience of being under the gaze or hearing the Others voice become disastrous for the subject and leads him to his own annihilation.
Keywords: psychoanalysis; narcissism; object a; voice; gaze